The Relationship of Compensation for Board of Directors and Board of Commissioners with Corporate Social Irresponsibility - Susilawati, Marlin Pernila; Harymawan, Iman (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
This study aimed at determining and analyzing the effect of compensation for board of directors and board of commissioners on corporate social irresponsibility. This study used 353 observations of 76 companies listed in the Indonesia Stock Exchange and the Global Reporting Initiative’s database of 2014-2018 and employed the ordinary least square regression analysis method. This study found that board compensation had positive and significant effect on corporate social irresponsibility. This study indicated that the higher the board compensation, the more the company tended to carry out corporate social irresponsibility due to lack of oversight in board decision-making or poor corporate governance practice and the boards’ desire to have them prospered regardless of the stakeholders. This study implied that company managers and stakeholders should determine the amount of board compensation.